Given the quadratic equation:

x^2 + 7x + 9 = 0

We need to solve for the roots using the quadratic formula.

Then we know that:

a =1 b= 7 c = 9

The formula for the roots is:

x = (-b +- sqrt(b^2 -4ac) ] / 2a

==> x1=...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Given the quadratic equation:

x^2 + 7x + 9 = 0

We need to solve for the roots using the quadratic formula.

Then we know that:

a =1 b= 7 c = 9

The formula for the roots is:

x = (-b +- sqrt(b^2 -4ac) ] / 2a

==> x1= ( -7 + sqrt(49 -4*1*9) / 2

= (-7 + sqrt(13) / 2

==>** x1= (-7/2) + sqrt13 / 2**

**==> x2= (-7/2) - sqrt13 /2**